Heavy oil production by carbon dioxide injection. Issue 3 (29th May 2013) - Gao, Changhong; Li, Xiangliang; Guo, Lanlei; Zhao, Fangjian
Abstract: With the depletion of light oil, heavy oil is becoming one of the most promising resources for meeting future energy consumption. Heavy oil resources are abundant, but the traditional water flooding method can only achieve less than 20% of heavy oil recovery. Thermal recovery has proven effective in producing heavy oil, but not suitable for many heavy oil formations that are either thin or buried deep underground. Carbon Dioxide injection is a 'win‐win' enhanced oil recovery (EOR) technique for many heavy oil fields. Injected CO2 not only increases heavy oil output, but also traps injected CO2 underground. Carbon dioxide effectively recovers heavy oil thanks to several mechanisms, including oil swelling, viscosity reduction, and blow‐down recovery. This review discusses the advances of CO2 flooding at both laboratory scale and field scale. Laboratory tests show that CO2 can significantly improve heavy oil recovery. Several field cases in the USA, Turkey, Trinidad, and China are reviewed. Field experiences show that CO2 flooding is a successful EOR method for heavy oil fields. However, some issues were encountered in field applications, such as early gas breakthrough, corrosion, CO2 availability, and high costs.